The role of arbuscular mycorrhizal fungi on ecosystem multifunctionality across phenological phases under warming in alpine meadows - Keyu Chen; Xiaoyue Yin; Luming Ding; Jingying Feng; Wubuli Subinuer; Changting Wang; Xinhua He; Chuangming Yang (CATENA, 2026)

Formation of casein particles from decalcified micellar casein concentrate by simulating human milk mineral composition: Colloidal structures and in vitro digestibility in model infant formula emulsions - Keyu Wang; Wenzhu Yin; Xiumei Tao; Dasong Liu; Yaowei Liu; Hua Liu; Yimiao Wang; Thom Huppertz; Joe M. Regenstein; Xiaoming Liu; Peng Zhou (Food Hydrocolloids, 2026)

Exogenous melatonin regulates hormone metabolism involved in delaying the ripening process in cherry tomato fruit during storage - Hang Zhang; Yue Wang; Jianhui Cheng; Wenbo Lei; Keyu Xu; Lilai Yin; Chen Huan; Shuling Shen; Lanying Yao; Xiaolin Zheng (Postharvest Biology and Technology, 2025)

In vitro gastrointestinal digestibility under infant conditions of bovine milk fat emulsions stabilized using decalcified micellar casein concentrate - Keyu Wang; Yuhan Zhao; Wenzhu Yin; Dasong Liu; Xiumei Tao; Yimiao Wang; Thom Huppertz; Joe M. Regenstein; Xiaoming Liu; Peng Zhou (Food Hydrocolloids, 2025)

p-chlorophenylalanine treatment accelerates tomato fruit ripening through hormone synthesis and glycolytic pathway during storage - Keyu Xu; Ran Yan; Hang Zhang; Lilai Yin; Wenbo Lei; Jianhui Cheng; Chen Huan; Yan Liu; Xiaolin Zheng; Shuling Shen (Postharvest Biology and Technology, 2025)

Cost effective selective separation of indium and germanium from zinc processing waste leach liquor using D2EHPA-YW100 synergistic system and selective stripping with HCl and NH4F - Chen Wang; Junxian Hu; Keyu Zhang; Shaoze Zhang; Yin Li; Yaochun Yao (Hydrometallurgy, 2025)

Coupled evolution of basin structure and fluids recorded by microfractures: A case study of deep-buried ordovician in the tarim basin - Jian Wang; Dongping Tan; Yingchang Cao; Jun Han; Haijun Yang; Yin Liu; Keyu Liu (Marine and Petroleum Geology, 2024)

Boosting activity on CoFe layered double hydroxide by doping and heterostructure as a bifunctional electrocatalyst for efficient overall water splitting - Jian Tang; Junxian Hu; Xuanli Chen; Bin Yang; Keyu Zhang; Yin Li; Yaochun Yao; Shaoze Zhang (Fuel, 2024)

Porous rod-like structured ternary nitride heterocatalyst Co3Mo3N/Ni3Mo3N for efficient and stable hydrogen evolution reaction - Jian Tang; Shaoze Zhang; Yixing Zeng; Bin Yang; Keyu Zhang; Yin Li; Yaochun Yao; Junxian Hu (Chemical Engineering Journal, 2024)

Investigation on catalytic distillation dehydrogenation of perhydro-benzyltoluene: Reaction kinetics, modeling and process analysis - Qinglian Wang; Keyu Le; Yi Lin; Wang Yin; Yixiong Lin; Maria V. Alekseeva; Vadim A. Yakovlev; Anton P. Koskin; Chen Yang; Ting Qiu (Chemical Engineering Journal, 2024)

Ibuprofen inhibits anaplastic thyroid cells in vivo and in vitro by triggering NLRP3-ASC-GSDMD-dependent pyroptosis - Haohao Guo; Runsheng Ma; Yifei Zhang; Keyu Yin; Gongbo Du; Fanxiang Yin; Hongqiang Li; Ziyang Wang; Detao Yin (Inflammopharmacology, 2024)
Pyroptosis is a novel type of proinflammatory programmed cell death that is associated with inflammation, immunity, and cancer. Anaplastic thyroid carcinoma (ATC) has a high fatality rate, and there is no effective or standard treatment. The disease progresses rapidly and these tumors can invade the trachea and esophagus, leading to breathing and swallowing difficulties. Hence, new treatment methods are greatly needed. Ibuprofen is a common drug that can exert antitumor effects in some cancers. In this study, we demonstrated in vitro and in vivo that ibuprofen can induce ATC pyroptosis. Hence, we treated C643 and OCUT-2C ATC cells with ibuprofen and found that several dying cells presented the characteristic morphological features of pyroptosis, such as bubble-like swelling and membrane rupture, accompanied by activation of ASC and NLRP3 and cleavage of GSDMD. Along with the increased release of LDH, ibuprofen treatment promoted apoptosis and inhibited viability, invasion, and migration. However, overexpression of GSDMD significantly inhibited ibuprofen-induced pyroptosis. In vivo, research has demonstrated that thyroid tumor growth in nude mice can be suppressed by ibuprofen-induced pyroptosis in a dose-dependent manner. In this research, we explored a new mechanism by which ibuprofen inhibits ATC growth and progression and highlighted its promise as a therapeutic agent for ATC.

Production of marker-free transgenic rice expressing tissue-specific Bt gene - Chengxiang Qiu; Jatinder Singh Sangha; Fengshun Song; Zhiyun Zhou; Ao Yin; Keyu Gu; Dongsheng Tian; Jianbo Yang; Zhongchao Yin (Plant Cell Reports, 2010)

High-resolution genetic mapping of bacterial blight resistance gene Xa10 - Keyu Gu; Jatinder Singh Sangha; Yin Li; Zhongchao Yin (Theoretical and Applied Genetics, 2008)